Beaverland : how one weird rodent made America - Philip, Leila (Twelve, 2022)
"In the rich naturalist tradition of H Is for Hawk and The Soul of an Octopus, Beaverland tells the tumultuous, eye-opening story of how beavers and the beaver fur trade shaped America's history, culture, and environment. Before the American empires of steel and coal and oil, before the railroads, there was the empire of fur. Beginning with the early trans-Atlantic trade in North America, Leila Philip traces the beaver's profound influence on our nation's early economy and feverish western expansion, its first corporations and multi-millionaires. As Leila's passion for this weird and wonderful rodent widens from her careful observation of its dams in her local pond, she chronicles the many characters she meets in her pursuit of the beaver: fur trappers and fur traders, biologists and fur auctioneers, wildlife managers, PETA activists, Native American environmental vigilantes, scientists, engineers and beaver enthusiasts. What emerges is a startling portrait of the secretive, largely hidden world of the contemporary fur trade and an immersive ecological and historical investigation of these animals that, once trapped to the point of extinction, have rebounded to become one of the greatest conservation stories of the 20th century. Now, beavers offer surprising solutions to some of the most urgent problems caused by climate change. Beautifully written and filled with the many colorful characters-fur trappers and fur traders and fur auctioneers, wildlife managers and biologists, Native American environmental vigilantes. She meets a Harvard scientist from the Blackfeet Reservation in Montana, using drones to create 3-dimensional images of beaver dams. She meets an environmental restoration consultant in the Chesapeake whose nickname is the beaver whisperer. Beaverland transports readers into scenes of beavers in their ponds and the scientists and fur trappers in pursuit of them, widening arcs of information to reveal the profound ways in which beavers and the beaver trade shaped history, culture, and our environment"--